Influence of Tithonia diversifolia and cattle manures on the growth and yield of sesame (Sesamum indicum L.) - Ehiokhilen Eifediyi; Henry Ahamefule; Felix Ogedegbe; Taiwo Agbede; Isiaka Kareem; Appiah Ajayi (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Much cattle manure and Tithonia are in abundance in the Guinea savanna of Nigeria where sesame has been found to do well. The cost of inorganic fertilizer is going beyond the reach of the average sesame farmer; the need therefore arises to synthesize farming practices that incorporate the rich organic materials locally available as a substitute for inorganic fertilizer for sustainable food production.Methods A study was conducted at the Teaching and Research Farm, University of Ilorin, Nigeria during the 2018 and 2019 cropping seasons, to evaluate the performance of sesame using T. diversifolia and cattle manures.  The following treatments; T. diversifolia (control, 0.9, 1.8 and 2.7 tha-1) and cattle manure (7.5, 15 and 22.5 tha-1) were used. Treatments were laid out in randomized complete block design, and replicated four times. Data on soil water content, growth and morphological characters and yield were collected.Result Results showed that T. diversifolia and cattle manures application improved soil water and nutrient contents, growth and yield attributes of sesame. Tithonia diversifolia applied at 2.7 tha-1 and cattle manure applied at 22.5 tha-1 gave the highest growth attributes, T. diversifolia applied at the rate of 1.8 tha-1 gave a yield of 547.2 kgha-1 and 527.6 kgha-1 in the 1st and 2nd seasons respectively. Cattle manure at 15 tha-1 gave a yield of 517.3 and 517.2 kgha-1 in first and second season respectively.Conclusion Farmers are advised to use T. diversifolia at the rate of 1.8tha-1 for high yield.